THE IMPACT OF EFFECTIVE SUPPLIER RELATIONSHIP MANAGEMENT ON FAST-MOVING CONSUMER GOODS MANUFACTURING FIRMS IN NAIROBI CITY COUNTY, KENYA - Silverman , Ominde Ph.D (International Journal of Allied Sciences (IJAS), 2023)
This extensive research project aimed to assess the correlation between supplier relationship management and the performance of Fast-Moving Consumer Goods (FMCG) manufacturing firms in Nairobi City County, Kenya. The study also highlighted the crucial role that the manufacturing sector plays in generating government revenue. Data was gathered from a total of 95 manufacturing companies in Nairobi City County, covering a diverse range of industries, including textiles, food, chemicals, wood and paper, building materials, water and drinks, breweries, metals, and toiletries. The findings of this research emphasize the importance of effective supplier relationship management in promoting the growth and profitability of FMCG manufacturing firms in Nairobi City County and the broader Kenyan economy